Improving Childrens’ Fine Motor Skills Through Collage Activities for Group A Children at Bustanul Ulum Kutowinangun Kindergarten, Sendang Agung District, Central Lampung Regency 2023/2024 Academic Year - Nukhayati, Nukhayati - (Journal of Teaching and Education, 2024)
This research was motivated by observational data on children's fine motor development activities, which showed that the learning outcomes of group A students at BUSTANUL ULUM KUTOWINANGUN Kindergarten, Sendang Agung sub-district, Central Lampung district in the 2023-2024 academic year were still low, whether they were rated BB or not. Developed in the majority of group A students. Fine motor skills are learning for preschool children, and they are related to physical skills involving small muscles and eye-hand coordination developed through routine activities and stimuli. Children's motor development develops gradually, so cooperation between teachers and parents is needed to stimulate children's fine motor development. In this research, the author chose collage as an activity that will help children develop their fine motor skills. Collage is an art technique of attaching various media to an object or pattern to create a new work of art. Using methods to stimulate children's fine motor development depends on the teacher's readiness and ability to provide simultaneous and continuous activities such as those in this research. This research is entitled "Improving the fine motor skills of young children in Group A through collage activities at Bustanul Ulum Kutowinangun Kindergarten, Sendang Agung District, Central Lampung Regency, Academic Year 2023/2024". In this research, the author used observation, interview and documentation methods. The author prepared several instruments before conducting research at Bustanul Ulum Kutowinangun Group A Kindergarten, Sendang Agung District, Central Lampung Regency. These instruments are classroom learning observation instruments, interview instruments with teachers and interview instruments with school principals.